Spermidine dietary supplementation and polyamines level in reference to survival and lifespan of honey bees - Srđana Đorđievski; Elvira L. Vukašinović; Tatjana V. Čelić; Ivan Pihler; Marko Kebert; Danijela Kojić; Jelena Purać (Scientific Reports, 2023)
Abstract Honey bee health has been an important and ongoing topic in recent years. Honey bee is also an important model organism for aging studies. Polyamines, putrescine, spermidine and spermine, are ubiquitous polycations, involved in a wide range of cellular processes such as cell growth, gene regulation, immunity, and regulation of lifespan. Spermidine, named longevity elixir, has been most analysed in the context of aging. One of the several proposed mechanisms behind spermidine actions is antioxidative activity. In present study we showed that dietary spermidine supplementation: (a) improved survival, (b) increased the average lifespan, (c) influenced the content of endogenous polyamines by increasing the level of putrescine and spermidine and decreasing the level of spermine, (d) reduced oxidative stress (MDA level), (e) increased the antioxidant capacity of the organism (FRAP), (f) increased relative gene expression of five genes involved in polyamine metabolism, and (g) upregulated vitellogenin gene in honey bees. To our knowledge, this is the first study on honey bee polyamine levels in reference to their longevity. These results provide important information on possible strategies for improving honey bee health by introducing spermidine into their diet. Here, we offer spermidine concentrations that could be considered for that purpose.